Initial Safety Parameter Evaluation of a PWR Loaded with Thorium and Reprocessed Fuel - Matheus Henrique dos Santos Araújo; Graiciany de Paula Barros; Geovana Loren da Cruz; Keferson Almeida Carvalho; Vitor Silva; Andre Augusto Campagnole dos Santos (Brazilian Journal of Radiation Sciences)
The once-through cycle (OTC) of nuclear fuel results in storing large quantities of high-radioactive isotopes. Alternatively, the closed cycle (CC), which involves reprocessing and reusing spent nuclear fuel, improves fuel utilization and reduces high-level radioactive waste. This study evaluates the feasibility of incorporating reprocessed fuel into a Pressurized Water Reactor (PWR) core. The PWR core was simulated based on the component dimensions, material definitions, and fuel compositions described in the available Benchmark for Evaluation and Validation of Reactor Simulations (BEAVRS). This core configuration originally contained only uranium-based fuels enriched at different levels, namely 1.6, 2.4, and 3.1 wt-% of 235U, and was used as a reference case.  Subsequently, the spent fuel of a PWR that attained a burnup of approximately 33,000 MWd/tHM and a cooling period of five years was theoretically reprocessed using two techniques: GANEX or UREX+. Both reprocessed fuels compositions were spiked with thorium dioxide. Then, four other PWR core configurations were simulated: two with the insertion of fuels reprocessed by the GANEX or UREX+ technique replacing uranium-based fuel enriched at 2.4% and two with the insertion of fuels reprocessed by the GANEX or UREX+ techniques replacing uranium-based fuel enriched at 3.1%. The Serpent code was used to simulate the reactor and assess the neutron flux, temperature reactivity coefficients and the impact of the boron concentration in the coolant on the effective multiplication factor. The findings indicate that using reprocessed fuel in this PWR core is not only feasible but also advantageous.